Reconsidering the goals of Irish corporate rescue law : identifying appropriate models and legal provisions suitable for a small open economy - Shanahan, Edmund (Trinity College (Dublin, Ireland). School of Law, 2016)
The Companies (Amendment) Act, 1990 as amended has proven to be one of the most controversial pieces of commercial legislation introduced in the State. This thesis investigates for the most part formal company rescue law in Ireland, that is the Companies (Amendment) Act 1990, as amended, and now found in the Companies Act 2014, so as to determine whether or not they are efficient mechanisms which are fit for purpose. The major conclusion of this thesis is that examinership to date has been successful in catering for a comparatively limited number of large or sometimes medium-sized Irish companies in distress. Those who designed it in its original form did not intend it for small companies or did not give the question much thought. If such is the range of consideration, examinership using the yardsticks developed by Finch is at least efficient and has been substantially a success. Moreover, prepack examinership of the kind exemplified in the Eircom rescue has proven itself to be very worthwhile. On the other hand, examinership to date has had very little to offer most Irish companies. Examinership lite, for its part, has yet to prove itself. Given the significant obstacles which still remain for small to medium-sized companies in the examinership process, it is difficult to be optimistic about the examinership lite development. The major argument of this thesis is that if examinership is to have meaning for small companies in Ireland, it should take the form of that outlined in the Donnelly proposal and to a lesser extent in the recommendation of the Company Law Review Group; that is to say an examinership mechanism which would be initiated by a non-judicial administrative procedure. This simplified procedure would extend only to the appointment of an examiner. It would remain necessary in this model to obtain the approval of the Circuit Court for any scheme of arrangement that the examiner would recommend. This would allow creditors to receive at least as much as they would in any other possible outturn. In addition, the small company in distress would be incentivised to use this approach because of the drastically reduced costs involved. The methodology employed has been that of functional comparative law. Planning and negotiation features of company rescue law in the three jurisdictions selected –that is, the United States, the UK and the Irish Republic- as well as the related moratoria have been analysed. The relevant case law and literature has also been considered.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin